PERANCANGAN APLIKASI MEDIA PEMBELAJARAN INTERAKTIF SEBAGAI SOLUSI PEMBELAJARAN DI MASA PANDEMI COVID-19 PADA MATA KULIAH ANIMASI GRAFIS DI PRODI FILM DAN TELEVISI ISI SURAKARTA BERBASIS ANDROID - Cito Yasuki Rahmad; Dedi Eko Nurcahyo (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2021)
ABSTRACT The Graphic Animation course is one of the compulsory subjects in the Film and Television Study Program, ISI Surakarta. Graphic Animation course consists of 2 credits taken by semester VI students. During the Covid-19 pandemic, graphic animation lectures did not work as expected. Interactive learning media emerged as a solution for students to be able to learn independently by following the instructions from the provided application. The purpose of this study was to create an android-based interactive learning media used in learning graphic animation courses and also to determine the effectiveness of using android-based interactive learning media used in learning graphic animation courses at the Film and Television Study Program ISI Surakarta. The method used in this study is the Research and Development (R & D) method with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The research data showed that from the questionnaire results of 24 students, the score for the content feasibility aspect got a score of 87% or in the very appropriate category, for the linguistic aspect it got a score of 82% or in the very appropriate category, for the presentation aspect it got a score of 81% or in the very category. appropriate, for the graphic aspect it gets a score of 75% or in the appropriate category, and for the task aspect it gets a score of 82% or in the very appropriate category.